Perancangan Interior Fasilitas Tunggu Kapal di Ekowisata Mangrove Wonorejo Surabaya - Stefanny Corry Angela (Intra, 2015)
As one of the tourist attraction in which located in Surabaya, Mangrove Forest is one of the ecosystems that has various benefit and potential. One of the conservation area of Mangrove is located in Wonorejo Surabaya. Unfortunately this tourist attraction area is poor in facility and activities that cannot be facilitated. Especially on the time of ship waiting for the cross over.The needed facility are the ones that can facilitate the ships waiting activity so that the visitors do not feel bored. The facility is a area includes a room for waiting which equipped with chairs and shelter, food corner are which are meant for selling foods, table for eating needs, mini library area with the mangrove books and magazines, the use and the benefit of it, speaker to announce the arrival of the ships or for music, and a room for the mangrove staff to control the waiting facility. This design will use bamboo as less used material in Indonesia in a conservative ecotourism object which is less desirable by the local people and still not yet fulfilled the needs of facility. By having an interesting and updated facility in Mangrove forest, especially in this cross over area, it is hoped that the amount of visitors will increase and they will be more comfortable having recreation in this place.